Q. 84.2( 5 Votes )

# In any triangle ABC, prove the following:

Answer :

Let a, b, c be the sides of any triangle ABC. Then by applying the sine rule, we get

⇒a = k sin A

Similarly, b = k sin B

And c = k sin C…..(i)

So, a + b = k(sin A + sin B)..(ii)

So the given LHS becomes,

Substituting equation (i) and (ii) in above equation, we get

Applying half angle rule,

And

Substituting equation (iii) and (iv) in equation (ii), we get

Hence proved

Rate this question :

In any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

a cos A + b cos B + c cos C = 2b sin A sin C = 2c sin A sin B

RD Sharma - MathematicsIn any triangle ABC, prove the following:

a(sin B – sin C) + b(sin C – sin A) + c(sin A – sin B) = 0

RD Sharma - MathematicsIn any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

a^{2} sin (B – C) = (b^{2} – c^{2}) sin A

In any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

b cos B + c cos C = a cos (B – C)

RD Sharma - MathematicsIn any triangle ABC, prove the following:

a^{2} (cos^{2} B – cos^{2} C) + b^{2} (cos^{2} C – cos^{2} A) + c^{2} (cos^{2} A – cos^{2} B) = 0

In a ∆ABC, if sin^{2} A + sin^{2} B = sin^{2} C, show that the triangle is right angled.